Hemotoxicity Induced by Chronic Chlorpyrifos Exposure in Wistar Rats: Mitigating Effect of Vitamin C - Suleiman F. Ambali; Joseph O. Ayo; King A. N. Esievo; Samuel A. Ojo (Veterinary Medicine International)
The study evaluated the ameliorative effect of vitamin C on chronic chlorpyrifos-induced hematological alterations in Wistar rats. Twenty adult male rats divided into 4 groups of 5 animals each were exposed to the following regimens: group I (S/oil) was administered soya oil (2 mL/kg b.w.), while group II (VC) was given vitamin C (100 mg/kg b.w.); group III was dosed with CPF (10.6 mg/kg b.w.); group IV was pretreated with vitamin C (100 mg/kg) and then exposed to CPF (10.6 mg/kg b.w.), 30 minutes later. The regimens were administered by oral gavage once daily for a period of 17 weeks. Blood samples collected at the end of the study revealed reduction in the levels of pack cell volume, hemoglobin, red blood cells, leukocytes (attributed to neutropenia, lymphopenia, and monocytopenia), and platelets in the CPF group, which were ameliorated in the vitamin C- pretreated group. The elevated values of malonaldehyde, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and neutrophil/lymphocyte ratio in the CPF group were restored in those pretreated with vitamin C. The study has shown that chronic CPF-induced adversity on hematological parameters of Wistar rats was mitigated by pretreatment with vitamin C.